Regulating global corporate capitalism - Picciotto, Sol. (New Delhi, 2011)
This analysis of how multi-level networked governance has superseded the liberal system of interdependent states focuses on the role of law in mediating power and shows how lawyers have shaped the main features of capitalism, especially the transnational corporation. It covers the main institutions regulating the world economy, including the World Bank, the IMF, the WTO and a myriad of other bodies, and introduces the reader to key regulatory arenas: corporate governance, competition policy, investment protection, anti-corruption rules, corporate codes and corporate liability, international taxation, avoidance and evasion and the campaign to combat them, the offshore finance system, international financial regulation and its contribution to the financial crisis, trade rules and their interaction with standards especially for food safety and environmental protection, the regulation of key services (telecommunications and finance), intellectual property and the tensions between exclusive private rights and emergent forms of common and collective property in knowledge.
Keywords: International economic relations